Multidetector Computed Tomography in Cases with Chest Trauma - Hilendarov, Atanas; Georgiev, A; Cherenkov, L (British Journal of Healthcare and Medical Research, 2023)
Introduction: Chest traumas are a significant cause of mortality and morbidity. They commonly occur in the younger population and are the most common cause of death in people between 25 and 40 years of age. Purpose: This article summarizes the place of MDCT in the diagnosis, examination technique and findings in injuries of the chest trauma patients. Methods: Multidetector computed tomography (MDCT) is considered to be the most effective imaging method in this field. Its advantages include especially high speed and high geometric resolution at any plane. The method allows us to view large parts of the body with minimal motion artifacts and to create accurate multiplanar and three[1]dimensional (3D) reformations. Results: MDCT allows us to view diagnosis significantly more accurate. One hundred and twelve patients are examined at the Emergency department. The injuries of the chest and intrathoracic organs are found. In 56 (50%) of all 112 patients included in our study, fractures of the ribs are the most common traumas. Also fracture of the scapula, sternum, extra pleural hematomas, pneumothorax, hemothorax, pulmonary contusions, laceration of trachea and bronchi, rupture of esophagus, diaphragmatic rupture and injuries of blood vessels are established. Conclusion: Because of its advantages MDCT has become the first[1]choice method in emergency chest trauma patients.